The effect of RORA (RAR-Related Orphan Receptor Alpha) receptors on litter size in Akkaraman sheep breed - Yigit, Serbulent; Kul, Selim; Aci, Recai; Keskin, Adem; Tuygun, Tugce; Duman, Esra (Shiraz Univ, 2023)
In this study, the relationship between RORA 23bp indel genotype and allele frequency with twin pregnancy, fertility, live weight and milk yield in 106 female Akkaraman ewes raised in Elazig province was investigated. In the study conducted in Elazig province, 10ml milk was collected from 106 Akkaraman sheep and DNA was extracted from these milk. In RORA 23bp indel genotype frequency, DD genotype was found more than ID and II genotypes and RORA 23bp indel in allele frequency, the D allele was found to be higher than the I allele. In both the first and second parity, the twinning rate was found to be lower. In both the first and second parity, the twinning rate was higher in the DD genotype, and it was observed that this genotype prominated middle livestock weight and milk yield. According to the results of our study, mutations in the RORA gene, which is a gene affecting reproductive efficiency in sheep, do not have a positive effect on fertility and twinning rate in Akkaraman sheep. To sum, this study provided theoretical references for the comprehensively research of the function of RORA gene and the breeding of Akkaraman Sheep. The 23-bp indel variants can be considered as molecular markers for litter size of sheep for marker-assisted selection breeding.
Keywords: Sheep; RORA; Insertion; deletion (Indel); Mmutation; Litter size